The correlation of skin color and gingival pigmentation patterns in a group of South Indians in Tamil Nadu, India - Deepa Ponnaiyan; L Gomathy; J A Anusha (Wolters Kluwer Medknow Publications, 2013)
Background: Melanin pigmentation of the gingiva occurs in all ethnicities. Excessive pigmentation is an esthetic concern that has increased awareness about depigmentation procedures. The purpose of the present study is to correlate skin color and gender with intensity and distribution of gingival melanin pigmentation in a group of South Indians for treatment strategies. Materials and Methods: A total of 200 male and female non-smoking healthy subjects were included aged 18-35 years. A clinical examination of gingiva was performed to assess the anatomic distribution of gingival pigmentation. The intensity of gingival pigmentation and phenotype of gingiva were also assessed. Subsequently, the skin color was visually examined and assessed as fair, wheatish brown and dark. Results: Six classes of gingival pigmentation were defined based on the anatomic distribution. Gingival pigmentation was observed as highest being in the attached gingiva and interdental papilla (25.4%) and least being in the marginal gingiva and interdental papilla (10.2%). Correlation between skin color and intensity of pigmentation was statistically significant, with dark skinned subjects having heavy gingival pigmentation. However, no correlation was found between gender and phenotype of the gingiva with intensity and distribution of pigmentation. Conclusion: South Indians predominantly have pigmentation in attached gingiva and interdental papilla and their skin color is positively correlated with the intensity of pigmentation. Incidence of pigmentation did not differ between the sexes. Majority of subjects had thick gingival phenotype. Anatomic delineation of gingival pigmentation and their contributory factors may help design treatment strategies in depigmentation procedures.